Tapping into the Skills of 21st-Century School Librarians: A Concise Handbook for Administrators - Church, Audrey P. (Rowman & Littlefield Publishers, 2015)
Strong school librarians positively impact student learning, and principal support is key. This concise handbook provides an overview of the roles of the 21st-century school librarian—teacher, instructional partner, information specialist, instructional leader, and program administrator. A valuable and informative resource, it gives principals the information they need to know in order to utilize the library program and librarian to the fullest potential to contribute to the instructional program of the school.